Process improvement on fish cleaning in fish cracker production - Mohd Syazali, Mohd Arif (2013)
Fish cleaning is performed at the first stage in fish cracker processing. Slow production rate at the fish cleaning process give a negative impact to the production of fish cracker. Traditionally, fish cleaning process is done by inconsistent procedure. Therefore, a new fish cleaning layout is designed to improve the process of this section. By using WITNESS, the current practice of fish cleaning process is simulated to analyze the problem in fish cleaning section. Using simulation technique, the productivity of current practice process is improved and then the result is compared with the current practice of fish cleaning workstation. Reducing distance of workstation to another workstation in the new design layout makes the average total idle and blocked condition decreased. The efficiency of the fish cleaning process can be increase about 34.28 %. Changing type of operation from single to the batch also help in increasing productivity of fish cleaning workstations. It is about to 107 % increasing in the productivity in the fish cleaning operation, a significant increase in the percentage. This study shows that by changing the layout and process type can give the optimal output for the production. Furthermore, the prediction of the output can be obtained by using the simulation, it help entrepreneur in decision making to rearrange or develop the new layout and process in order to meet the demand from customer